A Graphene/MXene-Modified Flexible Fabric for Infrared Camouflage, Electrothermal, and Electromagnetic Interference Shielding - Xianguang Hou; Ziyi Zang; Yaxin Meng; Tian Wang; Shuai Gao; Qingman Liu; Lijun Qu; Xiansheng Zhang (Nanomaterials, 2025)
Although materials with infrared camouflage capabilities are increasingly being produced, few applications exist in clothing fabrics. Here, graphene/MXene-modified fabric with superior infrared camouflage, Joule heating, and electromagnetic shielding capabilities all in one was prepared by simply scraping a graphene slurry onto alkali-treated cotton fabrics, followed by spraying MXene. The functionality of the modified fabrics after different treatment times was then tested and analyzed. The results indicate that the mid-infrared emissivity of the modified fabric decreases with an increase in the coating times of graphene and MXene. When the graphene/MXene-modified fabrics are prepared at loads of 5 and 1.2 mg/cm2, respectively, the modified fabrics have very low infrared emissivity in the 3–5 and 8–14 μm bands, and the surface temperature can be reduced by 53.1 °C when placed on a heater with a temperature of 100 °C (surface radiation temperature of 95 °C). The modified fabric also demonstrates excellent Joule heating capabilities; at 4 V of power, a temperature of 91.7 °C may be reached in 30 s. In addition, customized materials exhibit strong electromagnetic shielding performance. By simply folding the cloth, the electromagnetic interference shield effect can be increased to 64.3 dB. With their superior infrared camouflage, thermal management, and electromagnetic shielding performance, graphene/MXene-modified fabrics have found extensive use in intelligent wearables and military applications.